THE ROLE OF HUMAN PSYCHOLOGY IN LEARNING LANGUAGES. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Psychological aspects of the process of learning a foreign language are presented in the article will be considered. The role of psychology in education and its pedagogy and linguistics learns the connection with Psychological theories in teaching foreign languages in the article methods of application, professional language competence of the teacher, educational subject and factors taking into account the individual characteristics of students, especially foreign languages emphasizes the importance of learning motivation. This article is the main topic of education psychological-pedagogical analysis with its factors and components is given. In the article The definition of pedagogical psychology is close to its development and youth psychology connection is given. The main parts of pedagogical psychology are defined and the importance of pedagogical psychology in the teaching process and foreign language acquisition role is shown.